Analysing the Role of Intellectual Property Rights in Civil Law - Van Lodewijk Purba (Innovative: Journal Of Social Science Research, 2023)
Civil Law is one of the branches of law that regulates relationships between individuals or legal entities in society. One important aspect of Civil Law is the protection of property rights, including intellectual property rights. This research will analyse the role of IPR in Civil Law, identify the challenges and opportunities faced, and provide recommendations for improvement and further development in the protection of IPR in the future. This research is qualitative in nature. The techniques used to obtain information involved careful observation and meticulous note-taking, followed by analytical procedures such as data reduction, visualisation, and inference. The study arrived at the conclusion that the role of IPRs in Civil Law is crucial in protecting intellectual property rights and encouraging innovation. Despite the challenges faced in IPR protection, there are opportunities to improve and further develop the IPR protection system in the future.